Chemokine Signaling Guides Axons within the Retina in Zebrafish - Li, Qin (J Neurosci, 2005)
Chemokines are a large family of secreted proteins that play an important role in the migration of leukocytes during hematopoiesis and inflammation. Chemokines and their receptors are also widely distributed in the CNS. Although recent investigations are beginning to elucidate chemokine function within the CNS, relatively little is known about the CNS function of this important class of molecules. To better appreciate the CNS function of chemokines, the role of signaling by stromal cell-derived factor-1 (SDF-1) through its receptor, chemokine (CXC motif) receptor 4 (CXCR4), was analyzed in zebrafish embryos. The SDF-1/CXCR4 expression pattern suggested that SDF-1/CXCR4 signaling was important for guiding retinal ganglion cell axons within the retina to the optic stalk to exit the retina. Antisense knockdown of the ligand and/or receptor and a genetic CXCR4 mutation both induced retinal axons to follow aberrant pathways within the retina. Furthermore, retinal axons deviated from their normal pathway and extended to cells ectopically expressing SDF-1 within the retina. These data suggest that chemokine signaling is both necessary and sufficient for directing retinal growth cones within the retina.